2013
DOI: 10.1007/s10886-013-0286-z
|View full text |Cite
|
Sign up to set email alerts
|

Human Skin Volatiles: A Review

Abstract: Odors emitted by human skin are of great interest to biologists in many fields; applications range from forensic studies to diagnostic tools, the design of perfumes and deodorants, and the ecology of blood-sucking insect vectors of human disease. Numerous studies have investigated the chemical composition of skin odors, and various sampling methods have been used for this purpose. The literature shows that the chemical profile of skin volatiles varies greatly among studies, and the use of different sampling pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
177
0
9

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 200 publications
(194 citation statements)
references
References 87 publications
8
177
0
9
Order By: Relevance
“…Our group has recently demonstrated the potential of VOCs for skin physiology and SBF research where discriminating volatile emissions were observed before and after acute barrier disruption [22]. Collection and analysis of VOCs from skin is commonly achieved using solid-phase microextraction (SPME) [23] in combination with gas chromatography-mass spectrometry (GC-MS) [24] owing to the sensitivity of mass spectrometry, and the ease of performing headspace (HS) sampling with SPME.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has recently demonstrated the potential of VOCs for skin physiology and SBF research where discriminating volatile emissions were observed before and after acute barrier disruption [22]. Collection and analysis of VOCs from skin is commonly achieved using solid-phase microextraction (SPME) [23] in combination with gas chromatography-mass spectrometry (GC-MS) [24] owing to the sensitivity of mass spectrometry, and the ease of performing headspace (HS) sampling with SPME.…”
Section: Introductionmentioning
confidence: 99%
“…Various sampling methods have been used to analyse human skin volatiles (for review, see Dormont et al, 2013), such as solvent extraction of sweat samples or headspace collection of airborne skin volatiles onto adsorbent traps, usually following preliminary absorption on gauze or cotton pads, or sometimes on clothes that have been worn. Solid-phase micro-extraction (SPME) is a simple, sensitive, solvent-free technique originally developed for the monitoring of air pollutants and later extended to the sampling of volatiles from living organisms (Musteata and Pawliszyn, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…There is currently uncertainty concerning the nature of the odorants conveying such effects, and individual androstenes have been intensively assessed for their particular and specific influence on behavior (Havlicek et al, 2010;Wyatt and, 2015). We concede that androstenes are just one set of compounds within a much larger and complex mixture (e.g., Curran et al, 2005;Gallagher et al, 2008;Dormont et al, 2013), and therefore we do not wish to make claims about whether the effects reported in the literature are exclusively produced by androstenes. Other types of odorants present in the body odor mixture need indeed to be tested.…”
Section: Discussionmentioning
confidence: 99%